Optimasi Desain Gasket Karet Tipe Ring Profil C Flange Closed Groove dengan Metode Simulasi - Alamsyah, Fikrul Akbar; Choiron, Mochamad Agus; Purnowidodo, Anindito (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2016)
Gasket is one of important part in piping system to prevent leakage, especially in connection between pipes. The purpose of this study was to determine the optimal design on C profile rubber gasket based on contact width considering contact stress. Design parameter in this study were lips thickness (t)= 4; 4,5; 5 mm, lips length (l)= 5; 5,5; 6 mm, outer diameter (Ro)= 6,5; 6,7; 6,9 mm and inner diameter (Ri)= 2,5; 3; 3,5 mm. The observed value is contact width considering contact stress due to flange tightening and its measure by using finite element-based software. Mooney-Rivlin mathematical model used as rubber material model. Based on data from the simulation results, it can be obtained by using Taguchi Method; lips thickness (t) = 4,5 mm, lips length (l) = 6 mm, Outer Radius (Ro) = 6,9 mm and Inner Radius (Ri) = 3,5 mm.